Potent α-glucosidase and α-amylase inhibitory activities of standardized 50% ethanolic extracts and sinensetin from Orthosiphon stamineus Benth as anti-diabetic mechanism - Mohamed, Elsnoussi Ali Hussin; Siddiqui, Mohammad Jamshed Ahmad; Lee, Fung Ang; Sadikun, Amirin; Sue, Hay Chan; Soo , Choon Tan; Asmawi, Mohd Zaini; Mun , Fei Yam (BioMed Central, 2012)
Background: In the present study, we tested a 50% ethanolic extract of Orthosiphon stamineus plants and its isolated bioactive compound with respect to their α-glucosidase and α-amylase inhibitory activities. Methods: Bioactive flavonoid sinensetin was isolated from 50% ethanolic extract of Orthosiphon stamineus. The structure of this pure compound was determined on the NMR data and the α-glucosidase and α-amylase inhibitory activities of isolated sinensetin and 50% ethanolic extract of Orthosiphon stamineus were evaluated. Results: In vitro studies of a 50% ethanolic extract of O. stamineus and the isolated sinensetin compound showed inhibitory activity on α-glucosidase (IC50: 4.63 and 0.66 mg/ml, respectively) and α-amylase (IC50: 36.70 mg/ml and 1.13 mg/ml, respectively). Inhibition of these enzymes provides a strong biochemical basis for the management of type 2 diabetes via the control of glucose absorption. Conclusion: Alpha-glucosidase and α-amylase inhibition could the mechanisms through which the 50% ethanolic extract of O. stamineus and sinensetin exert their antidiabetic activity, indicating that it could have potential use in the management of non-insulin-dependent diabetes